Dampak Perubahan Sikap dan Metode Pembelajaran Guru terhadap Kinerja Siswa - Hafbi, Najwa; Sidik, Muhammad; Taufik, Muhammad; Zumaekal, Ahmad; Irfansyah; Wahyunengsih (Tarbawi, 2024)
The effectiveness of learning in shaping student performance has been a primary concern in educational research. This study examines the influence of changes in teacher attitudes and teaching methods on student performance in secondary education. This issue is driven by the evolution of the education landscape, where traditional teaching methods meet the need for more dynamic and student-centered methodologies. The research problem focuses on understanding how teacher attitudes toward learning change with innovative teaching methods, affecting learning outcomes. This reflects the increasing concern among educators about the gap between traditional teaching practices and the diverse needs of today's students. Using a quantitative approach by distributing surveys to students and teachers in different schools, this research explores the relationship between teachers and teaching methods and student activities. The results show a significant relationship between positive changes in teacher attitudes, the introduction of interactive and adaptive teaching methods, and improvements in student performance metrics. The conclusion drawn from the study emphasizes the importance of teacher attitudes and teaching methods in shaping student success. It underscores the importance of creating a positive, student-centered classroom environment where teachers can adapt and respond to individual learning needs. Additionally, the findings emphasize the need for continuous professional development initiatives to enhance teacher competencies in innovative pedagogical practices. The novelty of this scholarly work lies in comprehensively examining the correlation between teacher attitudes, teaching methods, and student performance